2021
DOI: 10.1186/s40795-020-00395-y
|View full text |Cite
|
Sign up to set email alerts
|

Promoting traditional foods for human and environmental health: lessons from agroecology and Indigenous communities in Ecuador

Abstract: Background The displacement of traditional dietary practices is associated with negative nutritional consequences for rural Indigenous people, who already face the brunt of both nutritional inadequacies and excesses. Traditional food (TF) consumption and production practices can improve nutritional security by mitigating disruptive dietary transitions, providing nutrients and improving agricultural resilience. Meanwhile, traditional agricultural practices regenerate biodiversity to support heal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 55 publications
1
23
0
1
Order By: Relevance
“…After adjusting for all candidate variables in the multivariable analysis, sex, site of waste disposal, bed net utilization, and intestinal parasitic infection remained statistically significant at a P value less than 0.05 (see Table 2 ). Accordingly, male children were 1.86 times [AOR = 1.86; 95% CI: 1.12, 3.09] more likely to be thin than their counterparts, which is consistent with other study results reported in Ethiopia [ 29 , 32 , 58 ]. Boys have less body fat and more muscle mass compared to girls; thus, they have a higher energy demand and burn more calories compared to girls.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…After adjusting for all candidate variables in the multivariable analysis, sex, site of waste disposal, bed net utilization, and intestinal parasitic infection remained statistically significant at a P value less than 0.05 (see Table 2 ). Accordingly, male children were 1.86 times [AOR = 1.86; 95% CI: 1.12, 3.09] more likely to be thin than their counterparts, which is consistent with other study results reported in Ethiopia [ 29 , 32 , 58 ]. Boys have less body fat and more muscle mass compared to girls; thus, they have a higher energy demand and burn more calories compared to girls.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, the magnitude of thinness in this study was lower than study results in the Philippines (27.8%) [ 56 ]. Similarly, the magnitude observed in schoolchildren from pastoralist and agropastoralist communities (22.9%) [ 21 ], Fogera district (37.2%) [ 47 ], Bahir Dar district (26.7%) [ 57 ], and Meket district (37.5%) [ 58 ] was lower. This variation might be due to the differences in the availability of health education programs for schoolchildren.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, strengthening and promoting the purchase and consumption of organic products is a challenge, since marketing efforts to highlight their virtues are scarce [ 34 , 35 ]. In relation to this, the correspondence between organic products’ production and legal policies is still incipient, since legally the planting and harvesting processes are protected with greater emphasis on industrialization and not on the more-traditional processes that benefit organic family farming and their markets [ 36 , 37 ]; In other words, organic producers need to offer their products in closed markets or with certain limitations, and not all consumers are aware of the existence of these markets and products [ 38 , 39 ], and therefore, very little is known about the behaviour and attitude of consumers towards these products.…”
Section: Introductionmentioning
confidence: 99%
“…As time passed, several factors have decreased the consumption of the communities' ancestral foods, which are foods that belong to a specific region and to the gastronomic heritage of that region, given the value that they contribute in terms of both preparation and consumption. For this reason, ancestral foods require knowledge and generate cultural identity [3,4]. Determinants of the loss of ancestral foods include the exhaustion of natural resources, the replacement of native crops by commercial ones, and changes in farming practices.…”
Section: Introductionmentioning
confidence: 99%